DYNAMICS OF BALINESE LANGUAGE IN THE TRANSMIGRATION AREA OF LAMPUNG PROVINCE - Seri Malini, Ni Nyoman (e-Journal of Linguistics; Vol. 5. Juli 2011 No. 2)
This study examines the dynamics of Balinese language in one of the Indonesia's transmigration areas of Lampung Province. Field research, interviews, and data recording were directly conducted in the territory of the Balinese (trans)migrants in the province . This province is the first transmigration destination with the greatest number of Balinese (trans) migrants. The results of this study indicate that the languages of interaction used by Balinese (trans) migrants are Balinese, Javanese, and Indonesian. Various linguistic events are colored by the use of Indonesian and Javanese including perceptive events involving dreaming, praying, quarrelling, and traditional-story telling. This illustrates that the mastery and use of such language is embedded in a series of mental processes, emotional, and psychological in the subconscious of the (trans) migrants. Other linguistic characteristics that emerged from Balinese spoken at the transmigration areas in Lampung are 1) socio-culturally there is ethnic identification in the lexical level by means of pronominal usage of KITA and DIA, 2) phonological and morphological interference, 3) high occurrence of code switching and code mixing between Balinese, Javanese, and Indonesian. Regarding language maintenance, Balinese migrants have positive behavior toward its native language (Balinese) which caused its maintenance to be adequate. The learning of Balinese for the sake of its inheritance and mastery by Balinese ethnics in the area is done informally. In terms of  language policy of the local government of Lampung Province, more weight is given to the development of Indonesian and Lampung language and literature while the other regional languages that co-exist in the province do not have clear status in terms of the pattern of their development.
Keywords: dynamics of the Balinese language, linguistic characteristics, language preservation, language policy